(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In this article, the logical structure of argumentation is the structure of proof, the interconnection of thesis and grounds in argumentation differs from that of proof in some aspects, the purpose of argumentation is to change trust and belief, the method of authorities is a study of interest in power and authority, and reasoning and proving opinions is a complex logical process. which discusses the use of one or more interconnected discussion systems.